2018
DOI: 10.1093/annweh/wxy082
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drift from a Conventional Axial Fan Airblast Sprayer in a Modern Orchard Work Environment

Abstract: Pesticide spray drift represents an important cause of crop damage and farmworker illness, especially among orchard workers. We drew upon exposure characteristics from known human illness cases to design a series of six spray trials that measured drift from a conventional axial fan airblast sprayer operating in a modern orchard work environment. Polyester line drift samples (n = 270; 45 per trial) were suspended on 15 vertical masts downwind of foliar applications of zinc, molybdenum, and copper micronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
2
14
0
5
Order By: Relevance
“…Fox et al [77], in experiments on apple trees, found that deposits on floss decreased with height at 7.5 m distance downwind, but were more uniform across all heights at 15, 30, and 60 m downwind. Kasner et al [78] reported that the distance from sprayed area, the height above ground, and the wind speed were significantly associated with drift level. Grella et al [64] found a good significant relationship between airborne drift and wind speed variables, especially for the maximum and mean wind speed.…”
Section: Airborne Spray Driftmentioning
confidence: 99%
“…Fox et al [77], in experiments on apple trees, found that deposits on floss decreased with height at 7.5 m distance downwind, but were more uniform across all heights at 15, 30, and 60 m downwind. Kasner et al [78] reported that the distance from sprayed area, the height above ground, and the wind speed were significantly associated with drift level. Grella et al [64] found a good significant relationship between airborne drift and wind speed variables, especially for the maximum and mean wind speed.…”
Section: Airborne Spray Driftmentioning
confidence: 99%
“…Conventional air-assisted (''airblast'') sprayers are the typical choice for pesticide application in orchards and nurseries. Airassisted sprayers are typically used to spray an entire farm at a constant rate (i.e., a set number of liters per hectare), regardless of variation in tree size or canopy characteristics (Hong et al, 2018), and these have been repeatedly shown to have considerable losses due to off-target spray and drift (Kasner et al, 2018;Nuyttens et al, 2011). In a comparison between total estimated leaf target and actual spray deposition in an orchard, 43% of the total amount sprayed by a traditional axial sprayer was applied to the foliage (Duga et al, 2015).…”
mentioning
confidence: 99%
“…Asam sianida akan larut dalam air (109; 110) , senyawa ini didalam air akanmembentuk ion CNdan ion H + .Senyawa dengan rumus kimia HCN cairan tak bewarna dan sangat beracun. Asam sianida memiliki bentuk molekul (115) linear (116)(117)(118)(119)(120) dengan momen dipol (121) Densitas (94; 125; 126) disebut juga dengan kerapatan merupakan massa per satuan volume suatu zat (211)(212)(213) pada suhu (127; 128) tertentu dan tidak hanya ditentukan gaya interaksi antar molekul (231)(232)(233)(234)(235) .Senyawa asam sianida memiliki sifat melarut sempurna pada air , dan sedikit larut dalam etanol. Ada beberapa faktor yang memengaruhi kelarutan suatu senyawa diantaranya sifat dari zat terlarut (solute) (139)(140)(141)(142)(143) dan pelarut (144) (solvent) (94; 129; 132; 145; 146) dimana zat terlarut yang bersifat polar (214)(215)(216) akan mudah larut dalam solvent (243)(244)(245)(246) atau yang disebut pelarut yang bersifat polar, begitupun sebaliknya, disini berlaku asas like dissolve like.…”
Section: Resultsunclassified